Clinical Characteristics and Prognostic Factors of Early and Late Recurrence After Definitive Radiotherapy for Nasopharyngeal Carcinoma - Li, Feng; Chen, Fo-Ping; Chen, Yu-Pei; Chen, Yue; He, Xiao-Jun; Huang, Xiao-Dan; Zheng, Zi-Qi; Zheng, Wei-Hong; Liu, Xu; Sun, Ying; Zhou, Guan-Qun (Frontiers in Oncology, 2020)
We investigated the clinical characteristics, prognostic factors, and post-recurrence prognostic factors of early and late recurrence patients for nasopharyngeal carcinoma (NPC) after definitive intensity-modulated radiation therapy (IMRT). This was a single-center retrospective analysis of patients in China from January 2010 to December 2015. The prognostic factors for overall survival (OS) and post-recurrence OS of early and late recurrence patients were identified using univariate and multivariate Cox regression analyses. Of the 9468 patients included, 409 (4.3%), 325 (3.4%) and 182(1.9%) developed purely local recurrence, purely regional recurrence and locoregional recurrence during follow-up, respectively. In purely local recurrence group, 192 patients (46.9%) developed early local recurrence (ETR), and 217 patients (53.1%) developed late local recurrence (LTR). Of the 192 ETR patients, multivariate Cox regression analysis revealed that age and gender were independent risk factors of OS, and post-recurrence best supportive treatment (PRBST) were associated with poorer post-recurrence OS. Of the 217 LTR patients, the results revealed that baseline value of EBV-DNA was an independent risk factor for OS, while PRBST were associated with poorer post-recurrence OS. In purely regional recurrence group, 183 patients (56.3%) developed early regional recurrence (ENR), and 142 patients (43.7%) developed late regional recurrence (LNR). Of the 183 ENR patients, multivariate Cox regression analysis revealed that alcohol abuse and TNM stage were independent risk factors of OS, while alcohol drinkers and PRBST were associated with poorer post-recurrence OS. Of the 142 LNR patients, PRBST were associated with poorer post-recurrence OS. In locoregional recurrence group, 87 patients (47.8%) developed early locoregional recurrence (ELR), and 95 patients (52.2%) developed late locoregional recurrence (LLR). Of the 87 ELR patients, multivariate Cox regression analysis revealed that N stage and TNM stage were independent risk factors of OS, and N2/3 stage and PRBST were associated with poorer post-recurrence OS. Of the 95 LLR patients, the results revealed that T stage was an independent risk factor for OS, while T3/4 stage and PRBST were associated with poorer post-recurrence OS. Patients with LTR/LNR/LLR demonstrate significantly better OS compared with patients with ETR/ENR/ELR, Nevertheless, post-recurrence OS between patients with ETR/ENR/ELR and LTR/LNR/LLR were not significantly different.